Hybrid zones in the European Alps impact the phylogeography of alpine vicariant willow species (Salix L.) - Pittet, Loïc; Marinček, Pia; Kosiński, Piotr; Wagner, Natascha D.; Hörandl, Elvira (Frontiers in Plant Science, 2025)
IntroductionIn the European Alps, Pleistocene climate oscillations resulted in geographical range expansions and restrictions of species. Postglacial recolonizations often result in secondary contact hybridization of vicariant species, thereby creating hybrid zones with patterns of introgression. Here, we compare the genetic structure of two secondary contact hybrid zones between two vicariant willow species pairs occurring in the European Alpine System. Supplemented by morphological and ecological data, we try to understand the factors shaping the hybrid zones and their influence on geographical range filling patterns.MethodsRAD sequencing and morphometric data were used to characterize biogeographical history, genetic diversity and the hybrid zone of each species pair. Vegetation relevés and species distribution models provided ecological context and support.Key resultsResults suggest that recolonization of the Alps happened from peripheral glacial refugia, resulting in broad secondary contact zones in the Eastern Alps in both species pairs. Both hybrid zones show introgression, but differ in symmetry and intensity of gene flow, in the type of introgressed loci, and in the geographical range. Habitat preferences and species distribution models do not indicate ecological barriers to recolonization.ConclusionsHybrid zones do not only affect the genetic structure of species by gene flow and introgression, but also appear to impact the biogeographical patterns of species.